Availability and reliability modeling of multicore controlled UPS for datacenter applications. (May 2016) - Addabbo, Tommaso; Fort, Ada; Mugnaini, Marco; Vignoli, Valerio; Simoni, Enrico; Mancini, Mario
Abstract: Modern data centers have to rely on continuous power to provide reliable and trustable services to their end users. Such power which comes from the main energy provider is most of the times supported by local uninterruptable power supply devices (UPS) which should therefore have a higher order of magnitude in terms of exploitability and reliability with respect to the hardware they are locally supporting. The reliability and availability performance of such systems must be therefore analyzed on both perspectives; the first one centered on the end user possibility to rely on a device every time it is needed and the second one aiming at a constant product performance improvement. These two different viewpoints can be far enough to lead to different product development strategies. In this manuscript a high efficiency modular UPS based on multicore control system for datacenter applications is presented and its reliability and availability figures discussed both from the designer and end user standpoints, under different operating conditions. Highlights: The possibility to provide designers with a specific architecture description. Addressing the design concept of a multicore controlled UPS. Comparison of multiple configurations in terms of RAMS parameters. Consideration on device availability vs end user availability.